Characterization of plasmid burden and copy number in Saccharomyces cerevisiae for optimization of metabolic engineering applications. Issue 1 (20th November 2012) - Karim, Ashty S.; Curran, Kathleen A.; Alper, Hal S.
Abstract Many metabolic engineering and genetic engineering applications in yeast rely on the use of plasmids. Despite their pervasive use and the diverse collections available, there is a fundamental lack of understanding of how commonly used DNA plasmids affect the cell's ability to grow and how the choice of plasmid components can influence plasmid load and burden. In this study, we characterized the major attributes of the 2 micron and centromeric plasmids typically used in yeast by examining the impact of choice of selection marker, promoter, origin of replication, and strain ploidy on conferred growth rates and plasmid copy number. We conclude that the 'plasmid burden', as demonstrated by a reduced growth rate, is primarily due to the choice of selection marker, especially when auxotrophic markers are utilized. The plasmid burden traditionally attributed to replication and maintenance of plasmid DNA plays only a minor role in haploid yeast yet is much more significant in diploid strains. The selection marker can also significantly change plasmid copy number. In fact, plasmid copy number can be influenced to some extent by all of the parameters tested. The information presented in this study will allow for more rational design and selection of plasmids for engineering applications.